Stimuli-responsive prodrug of non-steroidal anti-inflammatory drug diclofenac: self-immolative drug release with turn-on near-infrared fluorescence. Issue 56 (24th June 2022) - Sufian, Abu; Bhattacherjee, Debojit; Barman, Pallavi; Srivastava, Abhay; Thummer, Rajkumar P.; Bhabak, Krishna P.
Abstract : Reactive oxygen species (ROS)-responsive near infrared (NIR) fluorogenic non-toxic prodrug DCI-ROS is developed for the self-immolative sustained release of diclofenac (DCF ) with turn-on NIR fluorescence. Abstract : Reactive oxygen species (ROS)-responsive near infrared (NIR) fluorogenic prodrug DCI-ROS is developed for the self-immolative release of diclofenac (DCF) with turn-on fluorescence. The non-toxic prodrug exhibited turn-on red fluorescence with endogenous ROS in cancer cells and inhibited COX-2 expression in the inflammation-induced macrophage cells. The prodrug strategy thus would be helpful for the controlled fluorogenic delivery of DCF for inflammatory diseases.